Synthesis and Anticancer Activity of Novel 9-O-Substituted Berberine Derivatives - Viktor Milata (International Journal of Molecular Sciences, 2019)
Berberine is a bioactive isoquinoline alkaloid derived from many plants. Although berberine has been shown to inhibit growth and induce apoptosis of several tumor cell lines, its poor absorption and moderate activity hamper its full therapeutic potential. Here, we describe the synthesis of a series of 9-O-substituted berberine derivatives with improved antiproliferative and apoptosis-inducing activities. An analysis of novel berberine derivatives by EPR spectroscopy confirmed their similar photosensitivity and analogous behavior upon UVA irradiation as berberine, supporting their potential to generate ROS. Improved antitumor activity of novel berberine derivatives was revealed by MTT assay, by flow cytometry and by detection of apoptotic DNA fragmentation and caspase-3 activation, respectively. We showed that novel berberine derivatives are potent inhibitors of growth of HeLa and HL-60 tumor cell lines with IC50 values ranging from 0.7 to 16.7 µM for HL-60 cells and 36 to >200 µM for HeLa cells after 48 h treatment. Further cell cycle analysis showed that the observed inhibition of growth of HL-60 cells treated with berberine derivatives was due to arresting these cells in the G2/M and S phases. Most strikingly, we found that berberine derivative 3 (9-(3-bromopropoxy)-10-methoxy-5,6-dihydro-[1,3]dioxolo[4,5-g]isoquino[3,2-a] isoquinolin-7-ylium bromide) possesses 30-fold superior antiproliferative activity with an IC50 value of 0.7 µM and 6-fold higher apoptosis-inducing activity in HL-60 leukemia cells compared to berberine. Therefore, further studies are merited of the antitumor activity in leukemia cells of this berberine derivative.